Local Government Implementation of Business Licensing After the Issuance of the Job Creation Law - Najib, Ahmad Ainun; Rifa’i, Iman Jalaludin; Muktafa, M. Adil (Fakultas Hukum Universitas Sultan Ageng Tirtayasa, 2024)
Indonesia's 2020 Job Creation Law represents a critical legislative effort to boost investment by streamlining business licensing. This research addresses the pressing need to evaluate the real-world implications of this policy shift. Using a mixed-methods legal approach, we analyze the legal framework and its practical application. The novelty of this study lies in its focus on the socio-legal consequences of the new centralized, risk-based Online Single Submission system (OSS-RBA), which now manages all business licensing. Our findings show that while the reform has eased administrative burdens for businesses, the centralization of power away from local governments has unintendedly led to conflicts between businesses and local communities. This study's contribution is a critical examination of this legal reform, arguing that its positive economic goals may be undermined by unresolved social tensions at the local level.